Treatment outcome definitions in chronic pulmonary aspergillosis: a CPAnet consensus statement. Issue 6 (9th June 2022) - Van Braeckel, Eva; Page, Iain; Davidsen, Jesper Rømhild; Laursen, Christian B.; Agarwal, Ritesh; Alastruey-Izquierdo, Ana; Barac, Aleksandra; Cadranel, Jacques; Chakrabarti, Arunaloke; Cornely, Oliver A.; Denning, David W.; Flick, Holger; et al.
Chronic pulmonary aspergillosis (CPA) is an uncommon but dreaded complication of many respiratory diseases occurring in non- or mildly immunocompromised patients [1]. CPA affects approximately three million people worldwide, an estimation which is undoubtedly affected by under-reporting of this neglected disease [2]. The morbidity and mortality is high, with 5-year survival rates of 15–60% depending on comorbidities and age [3, 4]. The diagnosis of CPA is typically established on a combination of clinical, radiological and microbiological criteria all present for at least 3 months and the absence of an alternative diagnosis [1]. The most common form of CPA is chronic cavitary pulmonary aspergillosis (CCPA), besides other disease entities, including chronic fibrosing pulmonary aspergillosis (CFPA), Aspergillus nodule(s) and single aspergilloma. Subacute invasive pulmonary aspergillosis (SAIA), also called chronic necrotising pulmonary aspergillosis, usually occurs in moderately immunocompromised patients and comprises a more rapidly progressive clinical course (<3 months) [1]. Standardised and commonly accepted treatment outcome criteria for chronic pulmonary aspergillosis (CPA) can improve patient management by better comparability and understanding of CPA treatment studies: a CPAnet consensus statement. https://bit.ly/3paNfVC